THE ROLE OF MULTIMEDIA IN LEARNING THE FIELD OF CHRISTIAN RELIGION STUDIES ON STUDENT LEARNING CREATIVITY DURING THE COVID-19 PANDEMIC - Bangun Munte; Nurliani Siregar; Imelda Butarbutar; Bangun; Jojor Silalahi; Janwar Tambunan (Sean Institute, 2022)
The purpose of this study was to see how far the Role of Multimedia in Learning in the Field of Christian Religion Studyed on Student Creativity During the Covid-19 Pandemic. The number of samples is 38 people. This study uses a descriptive method, while the data analysis carried out in the hypothesis research is Pearson's product moment correlation with the data collection tool is a questionnaire for Variable X (The Role of Multimedia in Learning the Field of Christian Studies) and Variable Y (Student Learning Creativity). To find out the extent of the Role of Multimedia in Learning the Field of Christian Religion Studies on Student Creativity During the Covid-19 Pandemic, the Pearson Product Moment Correlation Statistics test. From the test results, it was obtained that the correlation (r) was 0.36 with a determination test of 12, then a